Being psychologically abused is not enough into ending a relationship: Sunk cost effect in intimate abusive relationships - Nunes-Costa, Rui; Serra, Mafalda; Sousa, Tânia; Leite, Ângela (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2020)
Our aim is to understand the role of the sunk cost effect in intimate abusive relationships. Results of a questionnaire, based on likely scenarios applied to 267 women, show that women in a relationship invest more time/days in a relationship than those who are not in a relationship. Also, an effect of scenario and of relationship status on sunk cost effect were found. Women spend more time in a non-violent scenario; also, they spend more time in a scenario of psychological violence than in one of sexual or physical violence. These results suggest that being in a relationship enhance the likelihood of committing sunk cost effect; prior investments in a relationship acquire more value for individuals in a current relationship where those efforts exist naturally.